2002
DOI: 10.1093/brain/awf283
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain reorganization for hand movement in patients with multiple sclerosis: defining distinct effects of injury and disability

Abstract: Previous work has demonstrated potentially adaptive cortical plasticity that increases with brain injury in patients with multiple sclerosis. However, animal studies showing use-dependent changes in motor cortex organization suggest that functional changes also may occur in response to disability. We therefore wished to test whether brain injury and disability lead to distinguishable patterns of activation with hand movement in patients with multiple sclerosis. By employing a passive as well as an active movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 51 publications
11
130
2
5
Order By: Relevance
“…5 Cortical reorganization or adaptation has been found to take place in patients with MS as a compensatory mechanism for functioning. 10,[12][13][14] This reorganization/adaptation is manifested by increased activation, as measured by fMRI, involving a broader range of cortical regions in these patients versus controls. Reddy et al 10 reported increased activation in the ipsilateral sensorimotor cortex with simple hand movements in patients with MS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…5 Cortical reorganization or adaptation has been found to take place in patients with MS as a compensatory mechanism for functioning. 10,[12][13][14] This reorganization/adaptation is manifested by increased activation, as measured by fMRI, involving a broader range of cortical regions in these patients versus controls. Reddy et al 10 reported increased activation in the ipsilateral sensorimotor cortex with simple hand movements in patients with MS.…”
Section: Discussionmentioning
confidence: 91%
“…Damage to both GM and WM components of the motor system has been reported in patients with MS. 10,11 Functional imaging studies have suggested that adaptive and/or compensatory mechanisms are involved in the attempt to maintain motor function during disease progression. 10,[12][13][14] These studies generally have demonstrated an increase in the extent of functional cortical activation in patients with MS versus controls during performance of specific tasks; this increased brain activation has been interpreted as cortical reorganization and/or adaptation. Given the role of GABA in other disease processes, we hypothesized that identifying a change in [GABA] within the sensorimotor cortex of patients with MS would provide us with additional information about the ongoing disease process and these compensatory mechanisms.…”
mentioning
confidence: 99%
“…Future studies of passive ankle dorsiflexion will determine if this paradigm can substitute for voluntary movement in subjects who cannot dorsiflex the ankle. Passive movement has shown some potential in several other neuroimaging studies (Loubinoux et al, 2003;Reddy et al, 2002) with significant correlations between dynamic sensorimotor activations for hand function in bilateral inferior BA 40 and continued gains.…”
Section: Locomotor Training-induced Plasticitymentioning
confidence: 99%
“…24,25 Various other MRI studies in MS have indicated recruitment of related brain regions after damage has occurred at a specific lesion. These changes in brain connectivity affect various functions including motor function, cognition and memory.…”
Section: The Importance Of Neuroplasticity In Multiple Sclerosismentioning
confidence: 99%